Triglycerides and risk of atherosclerotic cardiovascular disease: An update - Farnier, Michel; Zeller, Marianne; Masson, David; Cottin, Yves (Archives of cardiovascular diseases, 2021)
Low-density lipoprotein cholesterol is a well-known causal factor for atherosclerotic cardiovascular disease, and is the primary target of lipid-lowering therapy. There is, however, still a substantial risk of atherosclerotic cardiovascular disease events despite intensive statin therapy, and data from clinical trials suggest that an elevated concentration of triglycerides is a marker of residual cardiovascular risk on low-density lipoprotein-lowering therapy. Serum triglycerides are a biomarker for triglyceride-rich lipoproteins, and several lines of evidence indicate that triglyceride-rich lipoproteins and their cholesterol-enriched remnant particles are associated with atherogenesis. Moreover, genetic data in humans strongly suggest that the remnants of triglyceride-rich lipoproteins are a causal cardiovascular risk factor. Although lifestyle changes remain the cornerstone of management of hypertriglyceridaemia, a recent trial with high doses of the omega-3 fatty acid icosapent ethyl showed a significant reduction in cardiovascular events that was not explained by the reduction in triglycerides alone. In patients with elevated triglycerides, several novel drugs are in development to reduce the residual risk on statin therapy linked to an excess of atherogenic triglyceride-rich lipoproteins. In this review, we provide an update on the biology, epidemiology and genetics of triglycerides, and the risk of atherosclerotic cardiovascular disease.